Innovation, entrepreneurship and the academic context. Issue 3 (16th March 2021) - Lehmann, Erik E.; Meoli, Michele; Paleari, Stefano
ABSTRACT: This special issue aims to contribute to the understanding and evaluation of the processes through which innovative knowledge is created and translated to entrepreneurial technological advantage in higher education institutions. The papers presented here discuss new trends related to the impact of policies on innovation and entrepreneurial activity in universities, by providing a variety of insights from both an individual and an institutional perspectives and with reference to a number of different contexts and units of analysis.